Between conservationism, eco-populism and developmentalism: discourses in biodiversity policy in Thailand and Indonesia - Wittmer, Heidi; Birner, Regina (International Food Policy Research Institute, 2005)
The present paper analyzes the role of discourse in conflicts concerning nature conservation in tropical countries. We focus on the contested question as to whether and to which extent local communities should be allowed to live and use resources inside protected areas. Applying the concepts of belief-systems, story-lines and discourse coalitions, we analyze two empirical case studies dealing with this conflict: The first case study is concerned with a policy process at the national level that aimed at passing a community forestry law in Thailand to make the establishment of community forests in protected areas possible. The second case study deals with the proposed resettlement of a village from the Lore Lindu National Park in Sulawesi, Indonesia. In both cases, three discourses could be observed: a conservationist discourse, an eco-populist discourse, and a developmentalist discourse. The case studies show that the conservationists and the developmentalists were able to form a discourse coalition, which was challenged by the proponents of the eco-populist discourse. The analysis also demonstrates that establishing story-lines in the discourse can lead to the neglect of facts and problems that do not fit in either discourse. The paper draws attention to the role of science in the different discourses and concludes that scientists should become more aware of the role they play in the different discourses.